Fungos causadores de ferrugens (Pucciniales) em plantas da reserva florestal Adolpho Ducke, Amazônia central, Brasil - (:unkn) unknown (Museu Paraense Emilio Goeldi, 2016)
Fungi that cause rust on plants Adolpho Ducke Forest Reserve (ADRF), located in the city of Manaus (AM), were studied based on morphological characteristics of serums, spores and microstructures of taxonomic interest, and was also considered the specific nature of pathogens, in relation to the host plant. It identified 21 taxa belonging to eleven genera of Pucciniales order (Pucciniomycetes - Basidiomycota), classified in families: Chaconiaceae (Chaconia), Pucciniaceae (Puccinia), Pucciniosiraceae (Dietelia), Phakopsoraceae (Crossopsora), Raveneliaceae (Sphenospora) and Uropyxidaceae (Desmella, Edythea, Porotenus and Sorataea), and two anamorphic genera (Aecidium and Uredo). All identified species represent the first record for the study area, among them stand out the new records for Brazil: Uredo pusilla F. Kern, Thrust. & Whetzel; for Amazon: Dietelia duguetiae (Thrust.) Buriticá & J. F Hennen and the State of Amazonas: Aecidium xylopiae Henn, Chaconia heliconiae Berndt, Crossopsora piperis Berndt, F. O Freire & C. N. Bastos, Edythea palmaea (J. F. Hennen & Y. Ono). Cummins & Hirats., Porotenus biporus J. F Hennen & Sotão and Sphenospora smilacina Syd. The specimens studied were parasitized 20 genera of host plants, distributed in 13 botanical families (Annonaceae, Arecaceae, Bignoniaceae, Euphorbiaceae, Fabaceae, Heliconiaceae, Marantaceae, Moraceae, Piperaceae, Poaceae, Rubiaceae, Smilacaceae and Tectariaceae), among these, the Annonaceae family that stood out with five genera of host plants parasitized by five species of rusts. A key is presented for these species of rusts on Annonaceae. Descriptions of microstructures, photographic illustrations, geographical distribution and taxonomic comments are presented for these species and new records for Brazil, the Amazon and the State of Amazonas.
Keywords: Fungos; Ferrugens; Pucciniales; Basidiomycota; Biodiversidade; Pucciniomycetes; Taxonomia; Manaus - Amazonas; Amazônia Brasileira; Adolpho Ducke (Reserva florestal); CNPQ::CIENCIAS BIOLOGICAS::BOTANICA::TAXONOMIA VEGETAL